Sustainability Management in Gojek's Marketing Strategy: Impact on Brand Image and Customer Loyalty - Veta Lidya Delimah Pasaribu; Reza Khairul Hadi; Doni Wihartika; Hari Gursida (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2026)
Sustainability has become an important issue in the modern business world. Companies are required not only to pursue economic profits but also to pay attention to social and environmental aspects. This study aims to analyze the implementation of sustainability management in Gojek's marketing strategy and its impact on brand image and customer loyalty. The research uses a qualitative descriptive method with a literature study approach. The analysis results show that Gojek has successfully integrated the Triple Bottom Line principles into marketing activities through environmentally friendly programs, driver partner empowerment, and sustainability communication. These initiatives have proven to strengthen the company's positive image and increase customer loyalty. However, challenges remain, especially in terms of implementation costs and the still low consumer awareness.